The robot that stayed: understanding how children and families engage with a retired social robot - Zhao Zhao; Rhonda McEwen (Frontiers in Robotics and AI)
IntroductionSocial robots are increasingly introduced into homes as short-term educational or entertainment tools for children. However, their physical presence and social roles may persist long after their intended use has ended. This study explores how families continue to engage with a child-focused educational robot years after its original deployment.MethodsWe conducted a retrospective follow-up study with 19 families who participated in a 2021 in-home deployment of a reading companion robot for preschool-aged children. In 2025, we revisited these families through in-depth interviews to investigate how the robot had been integrated, re-purposed, or preserved over time.ResultsDespite the children outgrowing the robot’s instructional content, 18 families had retained the robot. Families described transitions in its role—from an educational device to a symbolic household member—characterized by emotional attachment, care-taking behaviors, and affection. The robot was re-framed as a memory object, integrated into new routines, or passed on ceremonially, akin to a “retirement.”DiscussionOur findings reveal three key themes explaining the robot’s enduring presence: (1) emotional attachment and personification, (2) symbolic and nostalgic value, and (3) practical re-purposing within household routines. This study contributes to long-term human—robot interaction literature by extending domestication theory and emphasizing the importance of designing for the full life cycle of social robots—including end-of-life transitions. It underscores how social robots can become meaningful companions and enduring artifacts of family identity, long after their functional use has ended.